The Implementation of Self-Assessment in Character Pillar Activities of Elementary School Students - Rakhmania, Raisa; Pratiwi, Yulia (Universitas Negeri Makassar, 2024)
Self-awareness is a person's ability to accept and understand their strengths and weaknesses so that they can develop their potential. Self-assessment is a tool that can be used to assess one's level of self-awareness. This research seeks to explore how 6-7-year-old students' awareness of themselves in assessing certain behaviors. The purpose of this study is to identify the application of self-assessment in character pillar activities in grade 1 students at SD Karakter, analyze students' perceptions of self-attitude and behavior on the tested character development aspects, and make recommendations for effective self-assessment development strategies to increase students' self-awareness. This study used a descriptive quantitative method with probability systematic sampling on 30 participants. The results show that self-assessment can measure students' self-awareness regarding generous, helpful, and cooperative attitudes and behaviors. Students and parents felt changes in behavior after the character pillar activities. Cooperation is the pillar concept that most often appears in students. This research proves that self-assessment can be used as a tool for student self-evaluation. Teachers can develop effective learning strategies based on students' self-assessment results.